Efektifitas Aplikasi Stimulasi Deteksi Intervensi Dini Tumbuh Kembang Anak Terhadap Pemantauan Pertumbuhan dan Perkembangan Anak Oleh Kader Di Posyandu - Winda Windiyani, Winda Windiyani; Ade Kurniawati, Ade Kurniawati; Fahrurizal Muldiana, Fahrurizal Muldiana; Erlinda, Erlinda (Karsa Husada Health Institute Garut, 2025)
Stimulation Program Detection Early Intervention Growth Kembang Anak is one of the service health important in Indonesia in effort improvement welfare babies , children and toddlers . Development child age under 5 years cause various type problems and solutions the problem How ways for children in Indonesia to experience appropriate growth and development? with age they . The number toddlers in Indonesia are quite big namely 10% of amount overall with various problem one of them disturbance growth and development . Children aged under 5 years cause various type problems and solutions problem How ways for children in Indonesia to experience appropriate growth and development? age . Purpose from study This give evaluation effectiveness application Stimulation Detection Early Intervention Growth Child Development Method Study This will use method quantitative with approach experimental control group design consisting of from group experiments that use 32 person and group application control of 32 people who used book guidelines implementation of SDIDTK at the level service basis . Data analyzed using nonparametric tests Statistical tests nonparametric Wilcoxon Signed-Rank Test was performed For know difference between pretest and posttest scores for each group . These results show that there is significant difference? between pretest and posttest scores on both group . In other words, there is improvement results meaningful learning? after given treatment , both in the group using application and groups that use book